Inflammation and Overweight in Peritoneal Dialysis: Is There an Association? - Antunes, Aline de Araujo [UNESP]; Vannini, Francieli Delatim [UNESP]; Martin, Luis Cuadrado [UNESP]; Balbi, André Luis [UNESP]; Ponce, Daniela [UNESP]; Nunes, Helio Rubens [UNESP]; Barretti, Pasqual [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP] (Taylor & Francis Inc, 2009)
More than 30% of the patients on peritoneal dialysis show chronic systemic inflammatory activity with high levels of C-reactive protein. The purpose of this cross-sectional study was to investigate the influence of the inflammatory state on clinical and nutritional markers in patients on peritoneal dialysis. Twenty-seven patients were included: mean age was 57.6 +/- 19 years, 48% were male, and median time on peritoneal dialysis was 16.0 (8.3; 35.8) months. Clinical, dialytic, laboratory, anthropometric and electric bioimpedance data were collected with the sample stratified for C-reactive protein. In patients, the levels of Interleukin-6 and tumor necrosis factor-a were higher, while adiponectin levels were lower than in healthy individuals (p <= 0.001), indicating the presence of inflammatory activity in the sample. When compared to patients with C-reactive protein < 1 mg/dL, those with = 1mg/dL showed higher body mass index (29.4 +/- 6.1 vs. 24.4 +/- 4.5 kg/m(2); p = 0.009), percent of standard body weight (124.5 +/- 25.4 vs. 106.8 +/- 17.9 %; p = 0.012), and percent of body fat as assessed by both anthropometry (31.3 +/- 9.9 vs. 23.9 +/- 9.1%; p = 0.056) and bioimpedance (38.9 +/- 6.3 vs. 26.2 +/- 12.6 %; p < 0.001). Patients with C-reactive protein = 1mg/dL also exhibited higher levels of ferritin (701 +/- 568 vs. 532 +/- 356 ng/mL; p = 0.054) and lower total lymphocyte count (median 1838 vs. 1638 mm(3); p = 0.001). In conclusion, higher body mass index and body fat markers were associated with C-reactive protein = 1mg/dL, and higher C-reactive protein was associated with immunocompetence impairment evidenced by the lower total lymphocyte count. Our findings confirm the relationship between inflammation, body fat, and immunocompetence, which may be superimposed potentializing the inflammatory status.
Keywords: dialysis; nutritional state; inflammation; body fat; overweight; lymphocytes count